1997
DOI: 10.1111/j.1439-037x.1997.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Population Density and Planting Pattern on the Yield and Yield Components of Leafy Reduced‐Stature Maize in a Short‐Season Area

Abstract: Maize hybrids that yield well, mature earlier with low grain moisture contents, tolerate higher population densities and take advantage of narrow row spacings better than the currently available hybrids would be more suitable for production in short-season areas. Leafy reducedstature maize hybrids, which have only recently been developed, have traits which address these criteria. The objective of this study was to evaluate the effects of different population densities (65 000 and 130000 plants ha"') and planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
(37 reference statements)
6
30
1
Order By: Relevance
“…This is consistent with the findings of Begna et al, (1997) who reported that higher grain yield among maize cultivar was due to the greater number of kernels that are formed in the ears which are more effective sink for carbohydrate synthesized in the leaves. It is also consistent with the findings of Ahmed and Sadek (1992) who reported that maize cultivars differ in their growth characters, yield and its components.…”
Section: Effects Of Variety and Spacing On Number Of Grains/cob Of Opsupporting
confidence: 82%
“…This is consistent with the findings of Begna et al, (1997) who reported that higher grain yield among maize cultivar was due to the greater number of kernels that are formed in the ears which are more effective sink for carbohydrate synthesized in the leaves. It is also consistent with the findings of Ahmed and Sadek (1992) who reported that maize cultivars differ in their growth characters, yield and its components.…”
Section: Effects Of Variety and Spacing On Number Of Grains/cob Of Opsupporting
confidence: 82%
“…High plant population affected yield components by reducing the number of ears plant -1 , kernels per ear and kernel weight. As plant population increased kernel weight is more stable than other yield components [80][81][82]. Source-sink relationships during grain filling effected the kernel weight [83].…”
Section: Plant Density Effect On Grain Yield Informationmentioning
confidence: 99%
“…At the same maturity, corn genotypes bearing the leafy trait have more leaves and leaf area above the ear, and are taller than conventional hybrids. A shorter vegetative period, longer grain-filling period, and higher yield potential were noted for Lfy than conventional genotypes, while reduced stature (rd1) types mature rapidly (Begna et al, 1997a(Begna et al, , 1997bModarres et al, 1997bModarres et al, , 1997cModarres et al, , 1998, making the Lfy and rd1 genotypes particularly well suited for short season areas. Most notable among corn genotypes bearing the Lfy trait are leafy reduced-stature (LRS, Lfy rd1) and leafy normal-stature (LNS, Lfy) genotypes.…”
Section: Leafy Reduced-stature Corn: Rapid Development Of Leaf Area Amentioning
confidence: 99%
“…The earliest studies of genotypes carrying the Lfy trait were focused on aspects of crop physiology (Modarres et al, 1997a(Modarres et al, , 1997bBegna et al, 1997aBegna et al, , 1999Begna et al, , 2000Dijak et al, 1999), mathematical characterization of canopy characteristics Dwyer, 1993, 1999), concentration of soluble sugars and starch and ear position and green leaf area duration . A few researchers have attempted to determine management requirements for Lfy hybrids, particularly their response to population density (Begna et al, 1999) and weed competition (Begna et al, 1997a(Begna et al, , 1997b(Begna et al, , 1999.…”
Section: Leafy Reduced-stature Corn: Rapid Development Of Leaf Area Amentioning
confidence: 99%
See 1 more Smart Citation